Metastatic papillary thyroid carcinoma in the soft tissue of the breast in a male patient: A case report - Maráčková, Veronika; Vomáčková, Katherine; Skanderová, Daniela; Mathew, Eva; Urbánková, Markéta; Veverková, Lucia (Oncology letters, 2025)
Papillary thyroid carcinoma (PTC) represents ~80% of all thyroid cancers, most frequently presenting in women in the third and fourth decade of life. The first clinical manifestation of PTC commonly includes a palpable mass in the thyroid area or cervical lymphadenopathy in cases of metastatic disease. Hematogenous distant metastases are a sign of an advanced stage of the tumour. The present study reported an extremely rare occurrence of solitary metastasis of a PTC in the left breast of a 63-year-old male patient, mimicking primary male breast cancer (MBC). The presence of a male breast lesion that did not follow the typical imaging criteria for MBC aroused suspicion of a different primary origin. The combination of imaging methods, laboratory findings and fine-needle aspiration techniques enabling cytological and histopathological examination, with the use of a wide panel of immunohistochemical markers, is crucial to establishing a definitive and correct diagnosis.
Keywords: mediastinal mass; breast metastasis; soft-tissue metastasis; PTC